Race and Racism: A Critical Dialogue - Elizabeth A. Peterson; Stephen D. Brookfield (Adult Education Research Conference, 2007)
This is a dialogue between Elizabeth Peterson, a black, female adult educator and Stephen Brookfield, a white male. The question was whether or not we could come together and engage in a critical dialogue about race and racism.